PENGAWETAN LIMA BELAS JENIS KAYU IRIAN JAYA SECARA RENDAMAN DINGIN - Sasa Abdurrohim; Abdurahim Martawijaya; Pipin Permadi (Pusat Penelitian dan Pengembangan Hasil Hutan, 1987)
Fifteen wood species from Irian Jaya with sample test pieces measuring 5 x 5 x 60 cm, and water content from 20. 0-21.4 percent, were subjected to cold soaking treatment, using 5 and 10 percent concentration of BFCA preservative, for three, five and seven days. Taking into account the penetration and retention requirement for wood use condition under roof and outdoor, without ground contact, the result indicates that matoa wood could not be treated with the schedule proposed in this paper. The other fourteen wood species could be treated with any of the treatment schedule (Table 4). However, two species (honggimako and senai) meet only the requirement for use under roof without ground contact.